The Effect of Service Quality And Customer Value on Customer Satisfaction at Celebrity Fitness Margo City - Kuswibowo, Christian (Indonesian Journal of Business and Entrepreneurship, 2022)
This research is aimed at analyzing the effect of both service quality and customer value towards customers’ contentment at Celebrity Fitness Margo City. The customers who are members of Celebrity Fitness Margo City are chosen as the object of this research. There were 75 respondents chosen by employing a quantitative descriptive method, thus, size were determined through incidental sampling technique due to certain considerations. The data was collected under a survey methods, by spreading questionnaires as the research instrument. Structural Equation Model with Smart-PLS analysis equipment is applied as an approach in this study. This study result shows that Service Quality owns a positive and crucial impact on Customer Contentment at Celebrity Fitness Margo City. In addition, the Customer Value performed a positive and significant effect towards Customer Contentment at Celebrity Fitness Margo City. On that account, it come to an end that both service quality and customer values play an important role in customer satisfaction, as the improvement in these both categories automatically increase the level these two key roles from the customer perspective. Keywords: service quality, customer value, customer satisfaction, SEM, celebrity fitness